Knowledge reuse and agile processes catalysts for innovation - Mitra, Amit 1949- (Information Science Reference, 2008)
"This book addresses flexibility of both business and information systems through component technology at the nexus of three seemingly unrelated disciplines: service-oriented architecture, knowledge management, and business process management. It provides practitioners and academians with timely, compelling research on agile, adaptive processes and information systems, and will enhance the collection of every reference library"--Provided by publisher.